UPAYA MENINGKATKAN HASIL BELAJAR MELALUI PEMBELAJARAN BERMAIN PERAN DENGAN MEMAINKAN DRAMA SINGKAT PADA MATERI GERAK TERHADAP SISWA KELAS VIIB - Ninik Sri Utami (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
This study aims to improve the learning outcomes of students of class VII B material motion by using model play a role by role-play. This study begins Monday, 27 April 2015 until the date of May 18, 2015 in two siklus.Hasil action showed that the activity of students increased from cycle 1 (58.82%), Cycle 2 (79.41%), and the positive response of students cycle 1 (73.53%), cycle 2 (88.27%), while the results of their study in cycle 1 (72.79) and cycle 2 (80.74).